The Effects of Non-Uniform Mechanical Compression of Lithium-Ion Cells on Local Current Densities and Lithium Plating. Issue 11 (9th November 2021) - Spingler, Franz B.; Friedrich, Sven; Kücher, Simon; Schmid, Simon; López-Cruz, Daniel; Jossen, Andreas
Abstract : Lithium-ion batteries can experience mechanical loads for a variety of reasons, including the rigidity of the cell casing itself, bracing of cell stacks in a module, which is generally due to limited space in the place of installation, or as a result of accidents or abuse. In all of these cases, and exacerbated by faulty manufacturing or assembly, the mechanical loads may be non-uniform across the cell surface. Here﻿, we present an analysis of﻿ the effects of such non-uniform mechanical loads on the current density distribution during charging and show that they can provoke localized lithium plating. Pressure-compression relationships of individual cell components were﻿ determined experimentally and implemented into a pseudo-3D axisymmetric electrochemical-mechanical cell model of a 2.1 Ah pouch cell by Kokam, South Korea. The modeling results were﻿ successfully validated by comparison to a post-mortem evaluation of pouch cells that were cycled while being locally compressed.